The Emerging Portuguese Maritime Mega Cluster: Endogenous Dynamics and Strategic Actions - Regina Salvador (European Regional Science Association (ERSA), 2014)
In these last four or five years, the creation of a Maritime Cluster in Portugal has been an issue of first political and economic relevance in the Country. The enlargement of the Continental Shelf under national jurisdiction into a total surface of 2.2 millions square kilometres (with a predictable high level of mineral, genetic and hydrothermal resources) ? particularly taking into account the economic crisis in current context ? awakes all kinds of hopes and ambitions. This "last big change in the World Map" ? in direct connection with the main guidelines of the Integrated Maritime Policy for the European Union ? requires the creation of a maritime mega-cluster. It should include both traditional (fishing, canning industry, ship building, maritime transports), and modern sectors (wave and tide energy, biotechnology), in a country that it is not known for a high level of social capital or its capacity of developing joint efforts. The current paper defines and presents the Maritime Cluster basic and most important characteristics in terms of main territories and regions. More specifically, the critical stage which corresponds to the Cluster initial emergence (during which the seeds for future economic growth are launched) has a strong dependence from different local conditions and the launch of specific processes. Starting with the assumption that geographical proximity and enterprises/institutions strategic cooperation promote competitiveness and innovation and, in consequence, the development, we propose to determine the existence of cooperation relationships and/or partnerships between activities connected with the maritime sector; if those relationships exist, are they partnerships at local, regional or national scale; and if recent trends point out towards innovation. The paper quantifies the sea cluster main intersectorial linkages, based on the integrated system of Portugal's Input-Output Matrix, to which we call Sea Input/Output Matrix (SIOM). It is also put in evidence the multiplier factors of direct, indirect and induced effects. Taking into consideration the final quantitative results, the authors present some remarks in terms of Employment, GVA and Investment in Portuguese Sea Cluster Economic Sectors. Finally, it is presented the preliminary results of a questionnaire that was launched among the members of the so called Sea Entrepreneurial Forum.
Keywords: 330; Maritime Cluster; Input-Output analysis; Extension of the Continental Shelf